The perception of affective touch in women affected by obesity - Tagini, Sofia; Scacchi, Massimo; Mauro, Alessandro; Scarpina, Federica (Frontiers in Psychology, 2023)
Pleasant and comforting bodily contacts characterized intimate and affective interactions. Affective touch informs us about others’ emotions and intentions, sustains intimacy and closeness, protecting from loneliness and psychological distress. Previous evidence points to an altered experience of affective touch in clinical populations featured by interpersonal difficulties. However, there is no investigation of affective touch in obesity despite this clinical condition is often associated with negative affective-relational experiences since childhood. This study aimed to provide the first evidence about the experience of affective touch in obesity by comparing fourteen women with obesity with fourteen women with healthy weight. Participants rated the pleasantness of both imagined and actual tactile stimuli, which consisted of i) soft-brush strokes, ii) touches of the experimenter’s hand, and iii) of a plastic stick (as control, non-affective, stimulation). Participants should report the pleasantness of each kind of touch. Moreover, we explored lifespan experiences of affective touch and interpersonal pleasure in social contexts through self-report questionnaires. No differences emerged for the pleasantness of affective touch (in both the real and imagery task) between the two groups. However, participants with obesity reported less frequent and less satisfying early experiences of affective touch when compared with the controls. Our results spoke in favor of a preserved experience of affective touch when experimentally probed in obesity, despite a limited early exposure to bodily affective contacts. We interpreted our results in the light of the social reconnection hypothesis. Nevertheless, we provided crucial methodological considerations for future research, considering that both the experimenter’s and the brush touch may not resemble adequately real-life experiences, in which affective touch involves intimate people.